Molecular characterisation and histopathological analysis of canine distemper virus in a Malayan tiger (Panthera tigris jacksoni) - Mohd Sadali, Muhammad Farris; Mariatulqabtiah, Abdul Razak; Salleh, Annas; Zahli, Nurul Izzati Uda; Tengku Azizan, Tengku Rinalfi Putra; Ahmad, Hafandi; Kaderi, Mohd Arifin; Hua, Khor Kuan; Abdul Wahab, Ridhwan; Abdullah, Ahmad Lutfi; Gani, Millawati; Mustaffa-Kamal, Farina (Korean Society of Veterinary Science, 2025)
Importance: Canine distemper virus (CDV) has a broad host range, spanning mammals of the order Carnivora and other orders, often proving fatal. The detection of CDV in a Malayan tiger (Panthera tigris jacksoni) in Malaysia in 2019 marks the first such case diagnosed in Malayan tigers, suggesting possible exposure from domestic animals or wildlife reservoirs. Objective: This study aims to describe histological manifestations and characterise the CDV strain in the tiger to determine its molecular epidemiology and postulate viral pathogenicity. Methods: Histopathology characterisation of the infected tissues were performed through haematoxylin and eosin and immunohistochemistry staining, respectively. We conducted virus isolation and titration in Chinese hamster ovarian expressing the dog signalling lymphocytic activation molecule (CHO-SLAM) cells. Reverse transcription polymerase chain reaction was performed to confirm the presence of CDV RNA, nucleotide and amino acid sequence analyses for comprehensive characterisation of the CDV strain. Results: Notable histopathological changes were observed primarily in the brain, lung, liver, kidney, spleen, and stomach, with viral antigens localised in the lung, liver, kidney, and stomach tissues. CDV-induced cell cytopathic effects yielding $4.27 × 10^6$ TCID$_{50}$/mL were observed at 48 h post-inoculation in CHO-SLAM cells. Phylogenetic analysis suggested that the virus originated from the Asia-1 clade. Notably, 549H and 519I mutations in the hemagglutinin protein were observed, indicating adaptation to a non-canid wildlife species. Conclusions and Relevance: Overall, this study enhances our understanding of the molecular characterisation and evolutionary dynamics of the CDV strain present in the Malayan tiger and serves as a benchmark for developing effective preventative measures to protect Malayan tigers and mitigate their risk of extinction.